Adverse Effects of Mercury Exposure in DDW Strain Mice during Organogenesis - Win Darmanto1 , Saikhu Akhmad Husen2 , Arif Abu Hasan3 , Raden Joko Kuncoroningrat Susilo4, Suhailah (Indian Journal of Forensic Medicine & Toxicology, 2020)
Mercury (Hg) was known as a teratogenic which is distributed in tissue. This study aims to determine theretention and embryotoxicity of Hg-exposed pregnant mice. Thirty female mice was treated with HgCl2(mercuric chloride). HgCl2 (5 and 6 kg/mg BW) was inducted in pregnant mice at 9 and 11 gestational days.Hg levels were measured in hair, uterus, liver, kidney, brain, blood, placenta, visceral fetus, and fetus brain onthe 18th day of gestation using the atomic absorption spectrophotometry (AAS) method. Embryotoxicity teston the fetus was carried out after the surgery took place. Scales and calipers are used to calculate fetal weightand crown rump length. Statistical tests were analyzed using the SPSS 21 program. The results showed thatthe liver, kidney, brain, visceral fetal, and fetal brain were significantly increased (P < 0.05) in the treatmentgroup at pregnant mice. Hg also produced a significant difference (P < 0.05) on the decrease in live fetuses,fetuses, body weight, and crown rump length and an increase in resorbed fetuses. Hg accumulation in thebody apparently can cause adverse effects in pregnant mice.